2022
DOI: 10.3390/foods11040590
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Balenine in Mouse Plasma after Administration of Opah-Derived Balenine by HPLC with PITC Pre-Column Derivatization

Abstract: We examined the absorption of balenine (Bal) in mouse blood after the administration of a high-purity Bal prepared from opah muscle. Using HPLC with phenyl isothiocyanate pre-column derivatization, we successfully isolated imidazole peptides and their constituents. We detected Bal and 3-methylhistidine (3-Me-His) in mouse blood 1 h after the administration of opah-derived Bal. The concentrations of Bal and 3-Me-His significantly increased to 128.27 and 69.09 nmol/mL in plasma, respectively, but were undetectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Sigemura et al demonstrated that balenine was detected in the plasma of mice at 1 h after oral administration of opah-derived balenine [ 36 ]. Notably, the concentration of balenine in plasma was higher than that of carnosine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sigemura et al demonstrated that balenine was detected in the plasma of mice at 1 h after oral administration of opah-derived balenine [ 36 ]. Notably, the concentration of balenine in plasma was higher than that of carnosine.…”
Section: Discussionmentioning
confidence: 99%
“…They were given a 1% w / w concentration of balenine-enriched extract diet (the concentration of balenine described in the previous study) or a normal diet for two weeks, from seven weeks of age. Shigemura et al reported that the administration of 200 mg/kg opah-derived balenine did not affect endogenous amino acid concentrations, including histidine and alanine in the blood [ 36 ]. The nutritional composition of each diet was the same as in a previous mice experiment [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anserine content was measured in heart tissue according to the method of Shigemura et al [41] with some modifications. In brief, heart tissue (100 mg) was added in phosphatebuffered saline and homogenized using Micro Smash TM MS-100R at 5000 rpm, at 4 • C and for 80 s. After centrifugation at 12,000× g, at 4 • C and for 10 min, the supernatant was added trichloroacetic acid (5%), vortexed, centrifugated at 12,000× g, at 4 • C and for 10 min and filtrated through a 0.45 µm hydrophilic nylon membrane.…”
Section: Measurement Of Anserine Content In Heart Tissuementioning
confidence: 99%